The Hybrid Gamification-Tpack (Technological Pedagogical Content Knowledge) Approach in Improving 4Cs Skills and Physical Literacy of Junior High School Students in Athletic Learning - Ishak, Muchamad; Hasmarita, Sony; Yusuf Nursyamsi, Muhamad; Gunawan , Gugun; Ferrari Valentino , Ricky; Meirizal , Yopi; Yunisal, Papat (STKIP Paasundan Press, 2025)
This study aims to analyze the effect of the Hybrid Gamification-TPACK approach on improving 4Cs Skills (Communication, Collaboration, Critical Thinking, Creativity) and Physical Literacy of 8th-grade students in athletic learning. Methods: This study used a quasi-experimental design with a pretest-posttest control group design. The research population was all 8th-grade students of SMPN 1 Cikao, Garut Regency, totaling 48 students who were sampled using total sampling technique. The sample was divided into experimental group (n=24) receiving Hybrid Gamification-TPACK learning and control group (n=24) receiving conventional learning. The intervention duration was 10 weeks with a frequency of 2 meetings per week. Research instruments used 4Cs Skills Assessment Rubric and Physical Literacy Assessment for Youth (PLAY) Tools. Data analysis used Independent Sample t-test and Paired Sample t-test with significance level α=0.05. Results: Results showed significant improvements in the experimental group for 4Cs Skills (pretest: M=64.25, SD=8.67; posttest: M=85.17, SD=6.42; p<0.001) and Physical Literacy (pretest: M=68.50, SD=9.23; posttest: M=87.33, SD=7.15; p<0.001). The control group also experienced improvements but not as significant as the experimental group. There were significant differences between experimental and control groups on posttest 4Cs Skills (p<0.001; Cohen's d=2.89) and Physical Literacy (p<0.001; Cohen's d=2.42). Conclusion: The Hybrid Gamification-TPACK approach proved effective in improving 4Cs Skills and Physical Literacy of junior high school students in athletic learning and can be an innovative alternative in 21st-century Physical Education learning